2017
DOI: 10.1186/s12014-017-9145-1
|View full text |Cite
|
Sign up to set email alerts
|

Glycated lysine-141 in haptoglobin improves the diagnostic accuracy for type 2 diabetes mellitus in combination with glycated hemoglobin HbA1c and fasting plasma glucose

Abstract: BackgroundRecent epidemiological studies indicate that only 30–50% of undiagnosed type 2 diabetes mellitus (T2DM) patients are identified using glycated hemoglobin (HbA1c) and elevated fasting plasma glucose (FPG) levels. Thus, novel biomarkers for early diagnosis and prognosis are urgently needed for providing early and personalized treatment.MethodsHere, we studied the glycation degrees of 27 glycation sites representing nine plasma proteins in 48 newly diagnosed male T2DM patients and 48 non-diabetic men ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 38 publications
5
29
1
Order By: Relevance
“…Glycation sites previously identified in plasma proteins of patients with diabetes were quantified after tryptic digestion of plasma samples and consecutive enrichment by boronate affinity chromatography, using a recently optimized method with multiple reaction monitoring on an electrospray ionization mass spectrometer (ESI‐MS), coupled on‐line to reversed‐phase high‐performance liquid chromatography (RP‐HPLC) . The validated protocol quantifies 30 glycation sites in 9 plasma proteins with sensitivities in the low nanomolar range and high interday precisions, that is, coefficients of variation (CVs) below 20%.…”
Section: Reasearch Design and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycation sites previously identified in plasma proteins of patients with diabetes were quantified after tryptic digestion of plasma samples and consecutive enrichment by boronate affinity chromatography, using a recently optimized method with multiple reaction monitoring on an electrospray ionization mass spectrometer (ESI‐MS), coupled on‐line to reversed‐phase high‐performance liquid chromatography (RP‐HPLC) . The validated protocol quantifies 30 glycation sites in 9 plasma proteins with sensitivities in the low nanomolar range and high interday precisions, that is, coefficients of variation (CVs) below 20%.…”
Section: Reasearch Design and Methodsmentioning
confidence: 99%
“…cFFA levels were compared among four different age‐matched cohorts, that is, 20 individuals with prediabetes, 48 patients with newly diagnosed T2DM, 48 long‐term controlled T2DM patients and 48 non‐diabetic individuals. FFA levels were also evaluated in combination with other routine anthropometric and laboratory chemistry parameters and the glycation degrees of 30 plasma protein glycation sites recently reported to improve diagnostic accuracy in T2DM . Additionally, the ratios of total cholesterol to HDL‐c (total‐c/HDL‐c), TAG/HDL‐c, and LDL‐c/HDL‐c and TAG levels as known predictors of CVDs, diabetic kidney disease (DKD) and ischemic heart disease (IHD) were studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein glycation is well characterized in mammals under several physiological conditions (Spiller et al, 2017). In humans (Homo sapiens), the formation of AGEs accompanies atherosclerosis and diabetes (Höhn et al, 2013).…”
Section: CMmentioning
confidence: 99%
“…Indeed, it was shown that seed proteins undergo this kind of modification during prolonged storage (Strelec, Ugarcic-Hardi, and Hlevnjak, 2008) and accelerated ageing of seeds (Wettlaufer and Leopold, 1991). It is important to note that resulting advanced glycation end products (AGEs) and advanced lipoxidation end products (ALEs) are known to interact with immunoglobulin-like receptors for advanced glycation end-products (RAGEs), and to trigger inflammatory response in mammals.…”
Section: Plant Sciencementioning
confidence: 99%